Form, Function And Meaning Of Kriya Ago For The Sakai Tribe Community In Duri, Bengkalis District - Syafrizal, Syafrizal (LANGGAM: International Journal of Social Science Education, Art and Culture, 2024)
This study aims to describe the form of Ago as a cultural object of the Sakai Tribe in Duri, Bengkalis Regency. explains the meaning contained in Ago as a Cultural Property and also explains the values ​​contained in Ago as a cultural object for value education for the Sakai Tribe. The research approach method was chosen to focus research so that the research results are in accordance with the research objectives and carried out scientifically. This research is field research with qualitative methods. The results of the research show that Ago is 1). Ago dimensional object made of wicker crafts, with a rectangular base and a circle on Ago's lips. 2) Ago has a practical and social function in the life of the Sakai people. 3). For the Sakai Tribe, Ago is a symbol of life and responsibility.